Biphasic Effect of Pirfenidone on Angiogenesis - Gan, Donghao; Cheng, Wenxiang; Ke, Liqing; Sun, Antonia RuJia; Jia, Qingyun; Chen, Jianhai; Xu, Zhanwang; Xu, Juan; Zhang, Peng (Frontiers in Pharmacology, 2022)
Pirfenidone (PFD), a synthetic arsenic compound, has been found to inhibit angiogenesis at high concentrations. However, the biphasic effects of different PFD concentrations on angiogenesis have not yet been elucidated, and the present study used an in vitro model to explore the mechanisms underlying this biphasic response. The effect of PFD on the initial angiogenesis of vascular endothelial cells was investigated through a Matrigel tube formation assay, and the impact of PFD on endothelial cell migration was evaluated through scratch and transwell migration experiments. Moreover, the expression of key migration cytokines, matrix metalloproteinase (MMP)-2 and MMP-9, was examined. Finally, the biphasic mechanism of PFD on angiogenesis was explored through cell signaling and apoptosis analyses. The results showed that 10–100 μM PFD has a significant and dose-dependent inhibitory effect on tube formation and migration, while 10 nM–1 μM PFD significantly promoted tube formation and migration, with 100 nM PFD having the strongest effect. Additionally, we found that a high concentration of PFD could significantly inhibit MMP-2 and MMP-9 expression, while low concentrations of PFD significantly promoted their expression. Finally, we found that high concentrations of PFD inhibited EA.hy926 cell tube formation by promoting apoptosis, while low concentrations of PFD promoted tube formation by increasing MMP-2 and MMP-9 protein expression predominantly via the EGFR/p-p38 pathway. Overall, PFD elicits a biphasic effect on angiogenesis through different mechanisms, could be used as a new potential drug for the treatment of vascular diseases.